2021
DOI: 10.1002/ehf2.13264
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and systemic embolism in patients with atrial fibrillation and heart failure according to heart failure type

Abstract: Aims This study aimed to elucidate the risk for stroke and systemic embolism (SE) in patients with atrial fibrillation and heart failure (HF) according to HF type. Methods and results A total of 10 780 patients with atrial fibrillation were enrolled in a multicentre prospective registry and divided according to HF type: no-HF, HF with preserved ejection fraction (EF) (HFpEF), HF with mid-range EF (HFmrEF), and HF with reduced EF (HFrEF). Each group included 237 age-matched and sex-matched patients (age, 69.0 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
(37 reference statements)
4
29
0
Order By: Relevance
“…Relative to HF with reduced ejection fraction (HFrEF), HFpEF may be associated with greater inflammation and oxidative stress and a higher risk of (AF-related) ischemic stroke (10). Indeed, in an age-and sex-matched registry study of Korean patients with AF, the annual incidence of stroke and systemic embolism in patients with HFpEF and HFrEF was 2.8% and 1.1%, respectively (11). Notably, the severity of HF symptoms may be associated…”
Section: Clinical Trial Evidence: Anticoagulation In Heart Failure and Sinus Rhythmmentioning
confidence: 99%
“…Relative to HF with reduced ejection fraction (HFrEF), HFpEF may be associated with greater inflammation and oxidative stress and a higher risk of (AF-related) ischemic stroke (10). Indeed, in an age-and sex-matched registry study of Korean patients with AF, the annual incidence of stroke and systemic embolism in patients with HFpEF and HFrEF was 2.8% and 1.1%, respectively (11). Notably, the severity of HF symptoms may be associated…”
Section: Clinical Trial Evidence: Anticoagulation In Heart Failure and Sinus Rhythmmentioning
confidence: 99%
“… 11) In a recent study from South Korea, a total of 10,780 AF patients were enrolled and divided according to HF type: no-HF (n=9,666), HFpEF (LVEF ≥50%; n=487), HF with mid-range ejection fraction (HFmrEF; LVEF 40–49%; n=263), and HFrEF (LVEF <40%; n=364). 12) The stroke/systemic embolism (SE) risk was higher in the HFpEF group than in the HFmrEF and HFrEF groups (hazard ratio [HR], 3.192; p=0.043), with E/e′ value as an independent risk factor. 12) Therefore, in ACCP and ESC guidelines, patients with either HFrEF or HFpEF would assigned 1 point for the “C” component.…”
Section: Stroke Risk Assessmentmentioning
confidence: 99%
“… 12) The stroke/systemic embolism (SE) risk was higher in the HFpEF group than in the HFmrEF and HFrEF groups (hazard ratio [HR], 3.192; p=0.043), with E/e′ value as an independent risk factor. 12) Therefore, in ACCP and ESC guidelines, patients with either HFrEF or HFpEF would assigned 1 point for the “C” component.…”
Section: Stroke Risk Assessmentmentioning
confidence: 99%
“…1 Although whether HF itself is a risk factor for stroke without the influence of atrial fibrillation (AF) is still controversial, recent studies have shown that stroke is considered one of the devastating outcomes in HF patients regardless of left ventricular ejection fraction (LVEF). 2 In addition, the presence of HF is also associated with worse outcomes and mortality after stroke.…”
Section: Introductionmentioning
confidence: 99%